Proposed modules on the concept environment for social studies II - Maningas, Antonio Alcabasa 1947- (1977)
The objective of the study was to propose modules on the concept environment for Social Studies II. The study attempted to look into the different elements of the new social studies and the underlying principles in individualized instruction that have to be considered in the production of instructional materials in the subject area. A task analysis of the content and objectives of the lesson has been made to guide the entire preparation of the modules. The study found out that individualizing the instruction strategy which emphasizes the importance of environment in the history and politics of a country, challenges and motivates the learner to study the material. The paper further emphasized how countries like Japan and the US achieved greatness and this was done though the presentation of facts in chart form. At the end of the phase, the student's achievements were rated through the Paper and Pencil Test and Checklist. The performance of the students served as the evaluation tool of the proposed module.